Autoimmunity in gestational diabetes mellitus in Sardinia: a preliminary case-control report - Murenu Michela; Sulis Simonetta; Motzo Costantino; Berria Rachele; Zedda Pierina; Garau Nicoletta; Portoghese Elaine; Orrù Marisa; Murgia Cinzia; Paoletti Anna; Melis Gian (BMC, 2008)
Abstract Background We previously reported a high prevalence (22.3%) of gestational diabetes mellitus (GDM) in a large group of Sardinian women, in contrast with the prevalence of Type 2 diabetes. Sardinia has an unusual distribution of haplotypes and genotypes, with the highest population frequency of HLA DR3 in the world, and after Finland, the highest prevalence of Type 1 diabetes and Autoimmune-related Diseases. In this study we preliminarily tested the prevalence of serological markers of Type 1 diabetes in a group of Sardinian GDM patients. Methods We determined glutamic decarboxylase antibodies (anti-GAD65), protein tyrosine phosphatase ICA 512 (IA2) antibodies (anti-IA2), and IAA in 62 GDM patients, and in 56 controls with matching age, gestational age and parity. Results We found a high prevalence and very unusual distribution of antibodies in GDM patients (38.8%), the anti-IA2 being the most frequent antibody. Out of all our GDM patients, 38.8% (24 of 62) were positive for at least one antibody. Anti-IA2 was present in 29.0 % (18 out of 62) vs. 7.1% (4 out of 56) in the controls (P < 0.001). IAA was present in 14.5% (9 out of 62) of our GDM patients, and absent in the control subjects (P < 0.001). Anti-GAD65 was also present in GDM patients, with a prevalence of 3.2% (2 out of 62) while it was absent in the control group (P = NS). Pre-gestational weight was significantly lower (57.78 ± 9.8 vs 65.9 ± 17.3 P = 0.04) in auto-antibodies- positive GDM patients. Conclusion These results are in contrast with the very low prevalence of all antibodies reported in Italy. If confirmed, they could indicate that a large proportion of GDM patients in Sardinia have an autoimmune origin, in accordance with the high prevalence of Type 1 diabetes.